Pathomorphological and molecular genetic features of diffuse gastric cancer - L. M. Mikhaleva; K. Yu. Midiber; V. V. Pechnikova; O. A. Vasyukova; M. Yu. Gushchin (Бюллетень сибирской медицины)
Gastric cancer (GC) is the 5th most common type of cancer in the world and the third leading cause of death from cancer. GC is a multi-factorial and morphologically heterogeneous disease. Currently, several morphological classifications of GC are used, however, for diagnosis, it is necessary to take into  account not only the morphological type of the tumor, but also its molecular subtype. According to the literature, the intestinal type of GC is most often associated with effects of environmental factors and is usually found in older  age groups in men, while diffuse gastric cancer (DGC) is a genetically determined disease which is more common in younger patients, with the same frequency among men and women.This review covers in detail GC, its classification by P.A. Lauren (1965), and its molecular subtypes characterized during the Cancer Genome Atlas project and examines the impact of certain risk factors on the pathogenesis of the disease, such as: H. pylori infection or Epstein – Barr virus. A separate section in this analytical work is dedicated to expression of the PD-L1 marker by tumor cells and the use of this parameter for prognosis and therapy of this disease. An essential part of the work is discussion of the features of intestinal and diffuse types of gastric cancer, which reflect not only the differences in classifications used in modern diagnosis, but also the relationship between the pathological pattern and the molecular subtype of gastric cancer.